Skiing efficiency in world-class distance-specialized and sprint cross-country skiers - Vesterinen, V.; Hynynen, E.; Mikkola, J.; Nummela, A. (Science and Skiing VII, 2018)
Work economy is an important factor of endurance performance. In a homogenous group of well-trained endurance athletes, work economy may even be a stronger predictor of endurance performance than VO2max (Coyle, 1995; Paavolainen et al., 1999). Work economy is often studied when the work rate is unknown, and is determined by the oxygen uptake at a defined submaximal speed. Gross efficiency (GE) is defined as the relation between mechanical work carried out and total energy expended (Rusko, 2003). However, in cross-country (XC) skiing, the mechanical work done is very difficult to measure due to varying terrain and snow conditions, but ski-specific laboratory testing using roller skis on treadmills enable the measurement of the work rate. Few studies have focused on mechanical efficiency in XC skiing (Bolger et al., 2016; Hoffman et al., 1995; Leirdal et al., 2013; Sandbakk et al., 2010; Sandbakk et al., 2013). Better skiers are shown to have greater GE and use longer cycle lengths than less successful skiers (Hoff et al., 1999; Sandbakk et al., 2010; Stöggl & Muller, 2009). In addition to technique, better neuromuscular performance characteristics have been reported to be associated with greater skiing economy (Hoff et al., 1999; Stöggl & Müller, 2009). Some physiological differences are reported between sprint and distance-specialized skiers due to different demands of performances. XC sprint skiers have been observed to be faster and stronger compared with distance-specialized skiers (Hebert-Losier et al., 2017). Because neuromuscular characteristics are related with work economy, it may be assumed that there can be differences in GE between XC sprint and distance-specialized skiers. To the best of our knowledge, no studies have compared skiing efficiency between world-class distance-specialized and sprint cross-country skiers. Sandbakk et al. (2010) investigated GE between world-class and national-level sprint skiers, and observed a higher skiing efficiency in world-class sprint skiers compared with national-level sprint skiers. The purpose of this study was to examine GE in roller-ski skating in worid-class distance-specialized and sprint XC skiers. In addition, the aim was to examine relationships between physiological characteristics and skiing efficiency.